Оцінка ефективності застосування загущеної присадками індустріальної оливи у вузлах тертя енергетичного устаткування - Коваленко, Тетяна; Івасик, Ярослав (Видавництво Львівської політехніки, 2013)
Polyfunctional lubricant performance properties indicates its significant impact on the longevity and efficiency of work of contact pairs. About 30% of the total energy produced is consumed to friction. The improvement of lubricant and efficiency of lubricating can reduce energy costs by 45%. Therefore, the correct choice of lubricant depends on energy consumption to overcome friction, wear of rubbing surfaces. The most economical way for the improvement of work of the friction units in different environmental conditions is the development of new lubricant compositions with the addition of an effective multifunctional additives as so base oils don't meet all of requirements put forward to them. The polymethacrylate additives with enhanced functionality were obtained in this work. The influence of the concentration of the additives on the viscosity-temperature, depressor and anti-wear properties of industrial oil I-20A were studied. Found that received additives improve the performance properties of oil-20A, respectively, contribute the reliable lubrication of the friction units in power plants at different natural conditions.
Keywords: присадки; індустріальна олива І-20А; експлуатаційні властивості; вузли тертя; енергетичне устаткування